2011
DOI: 10.1253/circj.cj-10-1129
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Coronary Artery Bypass Grafting in Obese Individuals - A Propensity Matched Analysis of Outcomes -

Abstract: Background: There is conflicting data regarding the impact of obesity on morbidity and mortality in patients undergoing isolated coronary artery bypass grafting (CABG). Methods and Results:Retrospective cohort analysis of patients who underwent CABG from January 1, 1995, through July 31, 2010 was performed. Patients were classified as obese or non-obese (body mass index ≥30.0 kg/m 2 and <30.0 kg/m 2 , respectively). The primary outcome was in-hospital mortality. Secondary outcomes included postoperative respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
1
24
0
8
Order By: Relevance
“…Postoperative drainage amounts were higher in normal patients compared to obese ones in various reports (5,(16)(17)(18). This association can be explained by increased levels of endothelial dysfunction markers like fibrinogen and von Willebrand factor in obese patients associated with hypercoagulability (19).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Postoperative drainage amounts were higher in normal patients compared to obese ones in various reports (5,(16)(17)(18). This association can be explained by increased levels of endothelial dysfunction markers like fibrinogen and von Willebrand factor in obese patients associated with hypercoagulability (19).…”
Section: Discussionmentioning
confidence: 84%
“…Saleh et al (2) studied the risk factors of prolonged ventilation in patients undergoing CABG and they found that BMI>35 was a predictor for prolonged ventilation while Christian et al (3) indicated that obesity was not a risk factor. Alam et al (5) in their review of 13.115 patients reported increased incidence of pulmonary complications in obese patients. In our study, we documented that intubation times were higher in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent form of manifestation of CAD in hospital admission, regardless of BMI, was the NSTEMI, a more serious medical condition than that found in a study comparing subjects with BMI < 30 and > 30 kg/m 2 , and finding a higher prevalence of UA in patients admitted to hospital (17) .…”
Section: Discussionmentioning
confidence: 65%
“…In general, it is known that the time of surgery is directly related to CPB time (19) . In some studies (17,20) in which there was statistically significant difference, the CPB time was lower in patients without excess of weight and overweight and higher in obese patients.…”
mentioning
confidence: 95%
“…In recent study, Ranucci [35] and Khairudin [36] found that obese patients are at higher risk for postoperative hypoxia and prolonged ICU stay. In contrast to the published literature, Alam et al [27] and Demir et al [37] reported comparable ICU stay and hospital stay times in obese and non obese patients after CABG. There are disparate results on the association between the obesity and postoperative renal insufficiency.…”
Section: Discussionmentioning
confidence: 74%